2019
DOI: 10.1016/j.dcn.2019.100706
|View full text |Cite
|
Sign up to set email alerts
|

Identifying reproducible individual differences in childhood functional brain networks: An ABCD study

Abstract: The 21-site Adolescent Brain Cognitive Development (ABCD) study provides an unparalleled opportunity to characterize functional brain development via resting-state functional connectivity (RSFC) and to quantify relationships between RSFC and behavior. This multi-site data set includes potentially confounding sources of variance, such as differences between data collection sites and/or scanner manufacturers, in addition to those inherent to RSFC (e.g., head motion). The ABCD project provides a framework for cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 87 publications
5
103
0
Order By: Relevance
“…Furthermore, because identification accuracy in both youth and adults was lower across a longer period of time and similar edges contributed to same day and 1.5-year identification accuracy, our results suggest that this reduction is not solely due to known developmental changes. Significant cognitive development occurs through adolescence (Larsen & Luna, 2018;Luna et al, 2015;Steinberg, 2005), in the context of evidence for stability at the group level in network properties Jalbrzikowski, Murty, et al, 2019;Marek et al, 2015;Marek et al, 2019). The stability in identification accuracy across development further supports that implication that network properties contain individualized foundational properties that define uniqueness.…”
Section: Identification Accuracy Is Similar In Youths and Adultsmentioning
confidence: 69%
“…Furthermore, because identification accuracy in both youth and adults was lower across a longer period of time and similar edges contributed to same day and 1.5-year identification accuracy, our results suggest that this reduction is not solely due to known developmental changes. Significant cognitive development occurs through adolescence (Larsen & Luna, 2018;Luna et al, 2015;Steinberg, 2005), in the context of evidence for stability at the group level in network properties Jalbrzikowski, Murty, et al, 2019;Marek et al, 2015;Marek et al, 2019). The stability in identification accuracy across development further supports that implication that network properties contain individualized foundational properties that define uniqueness.…”
Section: Identification Accuracy Is Similar In Youths and Adultsmentioning
confidence: 69%
“…To further test the reproducibility of univariate brain-phenotype associations, we determined the out-of-sample replication of brain-wide associations using established discovery (N=1,964) and replication (N=1,964) ABCD sets, matched across a broad range of demographic factors 29 (Extended data Fig. S9).…”
Section: Statistical Errors Are Ubiquitous In Typically Sized Brain-wmentioning
confidence: 99%
“…For network level analyses, correlations were averaged across previously defined canonical functional networks 59 . Inter-individual difference connectome-wide spatial components, which are not bound by network boundaries 29,33 , were computed by performing principal component analysis (PCA) on a matrix composed of all ROI x ROI pairs (edges) from each participant.…”
Section: Generation Of Resting State Functional Connectivity (Rsfc) Mmentioning
confidence: 99%
“…Whole-brain connectome-wide neurodevelopmental studies have found associations between resting-state functional network organization and behavioral traits (Satterthwaite et al 2015, Karcher et al 2019, Marek et al 2019, Pornpattananangkul et al 2019 . However, clinical decisions are made at the individual level (Milham et al 2017, Bzdok andMeyer-Lindenberg 2018) .…”
Section: Introductionmentioning
confidence: 99%